Improving Social Skills in a Child With Autism Spectrum Disorder Through Self-Management Training. Issue 4 (16th September 2015) - Liu, Yadan; Moore, Dennis W.; Anderson, Angelika
Abstract : The aim of this study was to assess the effects of a partially parent-implemented self-management intervention incorporating video-modelling for discrimination training on improving social skills in a child with autism spectrum disorder (ASD). The participant was a 9-year-old girl with ASD. A multiple baseline across behaviour design (no interruption, asking for opinions, and appropriately greeting unfamiliar adults) was used to assess the effects of the intervention. Results showed: (a) the intervention was associated with improvements in all target behaviours in the training setting with a strong overall treatment effect; (b) the behavioural gains were generalised to non-training settings and maintained in both fading and follow-up phases; and (c) social validity measured by the Behavior Intervention Rating Scale — Adapted version (pre- and postintervention) was high. The intervention was effective in improving social skills with this participant, with good generalisation and maintenance effects and high social validity.